Kualitas Program Layanan Homecare Terhadap Tingkat Kepuasan Pasien : Literature Review - Channe Esphi Royani Sirait; Grace Solely Houghty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Homecare is recovery, independence, fulfilling basic needs,choose the treatment nedded are called homecare, influences the success of health development. In overcoming health problems, health workers must be able to increase their professionalism in carrying out their duties to provide the best and highest quality services, so that patients and family members feel satisfied as measured by the factors. Purpose: This literature review research aims to find out how the quality of homecare service programs influences the level of patient satisfaction. Methods: There were 14 journals used in the literature review. Journal searches are carried out through Four databases : Google Scholar, Crossref, ProQuest, Emerald Insight.Results: Literature analysis shows that, there is a relationship between reliability, responsiveness, assurance, emphaty and tangible with the level of patient satisfaction.Conclusion: The quality of home services is influenced by several factors, the focus of quality measurement in Indonesia and several countries is similar. In other countries, quality seen in the nursing process, staff skills are called assurance. Quality is conceptualized as a continuous process, coordination of professional groups, prioritizing patient safety standards is called tangible, timeliness called responsiveness. In Indonesian quality is measured in five factors are tangible, responsiveness, reliability, assurance and empathy. These factors are most related to patient satisfaction in homecare services.